New records of the shrimp-like decapods Alpheus angulosus, Alpheus buckupi, and Axianassa australis from Maranhão, Brazil - Jeniffer N. Teles; Fernando L. Mantelatto (Nauplius, 2023)
Abstract We provide morphological and genetic evidence to establish the presence/occurrence of Alpheus angulosus, Alpheus buckupi, and Axianassa australis on the coast of Maranhão, Brazil. The specimens were collected in December 2019 by actively searching the estuaries and rocky shores of São Luís Island, northeast of Brazil. In addition to morphological analyses, two mitochondrial genes were obtained (Cytochrome C Oxidase I and 16S), and a phylogenetic analysis was conducted to verify the specimens’ identity. Accurate identification is an essential tool to obtain reliable information about the occurrence of the species and thus help assess biodiversity in a highly diverse region. These finding also serve to stimulate future studies in poorly studied areas as well as set a baseline for biodiversity conservation and preservation strategies.